Unitarity corrections in high energy QCD - Bartels, Jochen; Ewerz, Carlo (Journal of high energy physics, 1999)
The high energy limit of QCD is investigated in the generalized leading logarithmic approximation. We study unitarity corrections to the BFKL Pomeron containing t -channel states with up to six gluons. Special attention is given to the field theory structure of the corresponding multi-gluon amplitudes. We discuss the transition from two to six gluons in the t -channel.